Consumer acceptance of quality characterization of dehydrated strawberry product - Hasna, S. S.; Nugrahini, A. D.; Falah, M. A. F. (2022)
Strawberry is a horticultural fruit that has high nutritious content but a short shelf-life. Strawberries can be dried to extend their shelf-life. However, the drying process can cause quality change that can affect consumer acceptance. This research aimed to identify the quality of dehydrated strawberries based on consumer acceptance. Samples were produced using osmosis dehydration pre-treatment and dried by tray dryer. Imported and local products were used as a comparison. An untrained panelist was used to make a sensory analysis on five attributes on color, aroma, flavor, texture, and overall. Then, sample with highest acceptance value for each attribute were tested for the quality that consists of color, total sugar content, texture, and water content test. Based on the sensory analysis, sample with highest acceptance value for each attribute is as follows: local sample for color attribute, imported sample for aroma attribute, self- produced a sample for flavor, texture, and overall attributes. Based on the quality test, the dehydrated strawberry had discoloration due to maillard reaction. The sugar content, texture, and water content of the sample is in accordance with previous research. Sample with the highest acceptable value for overall is self-produced sample and can compete with local and imported sample.